2022
DOI: 10.1136/oemed-2022-108454
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of occupational skin cancer among outdoor workers in southern Spain: local pilot study

Abstract: ObjectiveOverexposure to ultraviolet (UV) radiation is the main preventable cause of skin cancer. Outdoor workers, exposed to the sun for many hours throughout their working lives, are at special risk. The aim of this study is to determine occupational photoexposure and photoprotection among outdoor workers employed by a municipality in southern Spain.MethodsCross-sectional descriptive study focusing on outdoor workers employed by the municipality of Fuengirola (in areas such as construction, gardening, urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(44 reference statements)
1
3
1
Order By: Relevance
“…On the whole, these results are in line with those of other groups that are especially vulnerable due to their high sun exposure, such as outdoor workers, 33 especially lifeguards, 34 and other athletes who participate in water sports. 27 Among the latter, no greater implementation of photoprotective measures to protect against their increased exposure was observed compared to other, less exposed groups such as healthcare workers 35 or educators.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On the whole, these results are in line with those of other groups that are especially vulnerable due to their high sun exposure, such as outdoor workers, 33 especially lifeguards, 34 and other athletes who participate in water sports. 27 Among the latter, no greater implementation of photoprotective measures to protect against their increased exposure was observed compared to other, less exposed groups such as healthcare workers 35 or educators.…”
Section: Discussionsupporting
confidence: 87%
“…The rates obtained from the analysis of works published between 1989 and 2015 were 38.16 (95% CI, 31.72–39.97) cases of melanoma per 100,000 person‐years and 113.05 (95% CI, 89.03–137.08) cases of BCC per 100,000 person‐years 38 . Although the lesions found require histological confirmation, the percentage of suspicious lesions is slightly higher to that found in examinations performed in other at‐risk groups such as the workers and guests at Costa del Sol hotels (2.2%: six lesions in 278 individuals), 39 but lower than the rate found among workers and players at golf courses (6.7%: 23 lesions in 242 individuals) 40 and outdoor workers (6.3%: eight lesions in 128 individuals, of which five were confirmed via biopsy) 33 …”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…An observational cross‐sectional pilot study conducted in Spain assessed sun exposure via dosimetry measurements and sun protective behaviors of municipal workers ranging in occupation from construction and maintenance to gardeners, urban cleaning personnel, and beach cleaning and maintenance members 48 . While beach employees and afternoon shift workers recorded the highest levels of UV exposure, the values did not differ significantly between shift times or occupational sectors.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers found that a one-point increase in Workplace Sun-safety Culture Score (range: 12 points) was associated with a 0.16 higher Personal Sun-Protection Score (P < 0.001), and a onepoint increase in Workplace Provision Score (range 4 points) was associated with a 0.14 higher score (P < 0.001). 34 Question 48 While beach employees and afternoon shift workers recorded the highest levels of UV exposure, the values did not differ significantly between shift times or occupational sectors. Of the 128 study participants who agreed to dermatologic check-ups, 79.7% demonstrated evidence of actinic lentigines, while 8.6% exhibited actinic keratoses.…”
Section: Question 1 How Is Ultraviolet Radiation Measured?mentioning
confidence: 87%